Identification Of Salmonella Enterica Serovar Typhi Putative Virulence Factors Using A Yeast Morphology Assay - Pong, Sze Yen (2018)
Typhoid fever is a symptomatic bacterial infection caused by Salmonella enterica serovar Typhi that usually occurs due to poor sanitation and hygiene. The identification of novel virulence factors (VF) of S. Typhi will allow for better understanding of the pathogenesis of typhoid infection and potentially help disease management. There are still unidentified VFs and for those already reported, their roles in pathogenesis are still not completely understood. In this study, Saccharomyces cerevisiae was used as a model organism to identify putative S. Typhi. A total of 192 putative VFs were selected from the proteome of S. Typhi CT18 through cross-reference with published literature and database searches. Then, the selected VF genes were cloned and expressed in yeast in a 96-well plate format. A total of 190 putative VFs were cloned into plasmid with green fluorescent protein and expressed in yeast. By using a microplate growth assay that measures optical density of liquid culture, nine putative VFs were found to inhibit the yeast growth. Then the putative VF proteins’ localization in yeast were observed and categorised, one effector protein localized at cell membrane and four effector proteins each at endoplasmic reticulum and cytoplasm. Result of the morphology assay showed that five of the putative VFs undergo filamentous growth and 98 putative VFs showed significant cell size changes. In conclusion, yeast morphology observation is essential to identify putative VFs that can interfere with yeast intracellular process but not necessarily inhibit yeast growth.